The Significant Of Innovation and Its Imperative Part in Development, Survival and Success of Organizations - Dr. Swarooprani K (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Innovation is one of the most significant concerns of each association and its role in the growth and coordination of the market is absolute. Innovation in all human areas is appropriate from creation development, methods of organization, ways of liability works and etc. In all of definition used for innovation, shifting or improvement of the method or product are common. Innovation is a procedure that begins with introduction to plan of an idea and will become a new purpose and so it different from creation. The major point is that novelty is different from originality. In this paper the significant of innovation and its vital role in growth, survival and winner of organizations is discussed.
Keywords: Innovation; Growth; healing; Creativity